Self-limiting caries excavation with a polymer bur: Adhesive bonding to residual dentin. (April 2020) - Wohlleb, Teresa; Kaisarly, Dalia; Rösch, Peter; Kunzelmann, Karl-Heinz
Abstract: Objectives: The aim of this study was to evaluate the bonding of an universal adhesive to residual affected dentin after polymer bur excavation of natural caries lesions in human teeth. Materials and methods: Caries excavation with a polymer bur and with a carbide bur were compared. A microtensile bond strength (μ-TBS) test was performed in a split-tooth design (n = 20/group). A universal adhesive (Scotchbond Universal, 3M-Deutschland, Neuss/Germany) was applied in either self-etch (SE) or total-etch (TE) mode. Qualitative and quantitative margin analysis was assessed before/after fatigue simulation (n = 8/group). Micro-CT examination was performed before/after polymerization of class-II restorations (Tetric EvoCeram BulkFill, Ivoclar-Vivadent, Schaan/Liechtenstein) (n = 6/group). Volumetric shrinkage and shrinkage vectors were calculated. The internal interface was analyzed under scanning electron microscopy after cutting the teeth. Results: The μ-TBS test revealed no significant difference between excavation methods. Mean tensile strengths (MPa) were: polymer-bur/SE = 16.0, polymer-bur/TE = 16.7, carbide-bur/SE = 15.5, carbide-bur/TE = 20.3, dentin/SE = 13.9, dentin/TE = 24.1. Margin analysis rated all groups >99% of perfect margin in dentin and enamel, no influence of excavation methods was found. Micro-CT examination revealed no difference between groups concerning volumetric shrinkage (1.9–2.5%). The shrinkage direction was towards the bonded area. Polymer bur excavation resulted in an irregular surface and thicker smear layer than with carbide bur. Conclusion: Caries excavation with a polymer bur does not negatively affect bonding performance to residual affected dentin. Etching with phosphoric acid can further strengthen the interface.